2020
DOI: 10.1159/000505508
|View full text |Cite
|
Sign up to set email alerts
|

Olive Leaf (<b><i>Olea europaea L. folium</i></b>): Potential Effects on Glycemia and Lipidemia

Abstract: Background: Olive tree (Olea europaea, Oleaceae) leaves have been widely used in traditional herbal medicine to prevent and treat various diseases especially in Mediterranean countries. They contain several potentially bioactive compounds that may have hypoglycemic and hypolipidemic properties. Summary: The literature has recently been attempting to define the relationship between olive leaf (Olea europaea L. folium) polyphenols and a number of health problems. Oleuropein, the basic phenolic compound of olive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 50 publications
(89 reference statements)
1
36
0
Order By: Relevance
“…In addition, in the traditional culture of many Italian regions, olive leaves, as well as olive oil, have played the role of good luck against the evil eye [1]. Beyond the symbolic properties attributed to olive leaves, they have historically had a pharmacological role in Mediterranean countries and are widely used in traditional herbal medicine to prevent and treat various diseases [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the traditional culture of many Italian regions, olive leaves, as well as olive oil, have played the role of good luck against the evil eye [1]. Beyond the symbolic properties attributed to olive leaves, they have historically had a pharmacological role in Mediterranean countries and are widely used in traditional herbal medicine to prevent and treat various diseases [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds in olive leaves are major contributors to their antioxidant effect [27]. According to Acar-Tek and Agagündüz [28], the toxicity studies suggest that olive leaf is generally safe, even at high doses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neuronal and microvascular endothelial cell damage as induced by hyperglycemiamediated oxidative stress contributes to the pathogenesis of neuropathy with loss of protective sensation(23). It has been reported that the antioxidants that directly remove free radicals can reduce the formation or progression of ROS reactions, and thus may improve diabetic neuropathy status by reducing oxidative stress(16).However, the antioxidant effect of olive leaves in the literature is remarkable[3,8]. In our model, antioxidant status was indicated by serum LOOH and thiol levels.…”
mentioning
confidence: 78%
“…Therefore, the number of studies on alternative treatments using medicinal plants has increased recently (2). Among these medicinal plants, olive tree leaves, which are an important source of antioxidants, have been used in traditional treatments for centuries in regions where olives grow (3). Moreover, there are numerous academic studies reporting the benefits of olive leaf in terms of health (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation